Case studies on the water use of large scale mining in the Philippines - Cielo Magno; John Christopher Lawrence Morillo (University of the Philippines, School of Economics (UPSE), 2019)
Water use is one of the most critical sustainability issues of the mining sector. It is important in each stage of the mining life cycle. The water use of the mine can introduce significant ecological changes. It can compete with the water use of households living in the community and other economic activities in the area. We look at the water use of two large scale mining companies and communities in Didipio, Nueva Viscaya and Taganito, Surigao del Norte. We compare water extraction with various factors such as mineral production, land use, rehabilitation, mine development, and environmental concerns. Based on our initial findings, the rate of water extraction of the two mines is significantly correlated with the level of mine development, rehabilitation and pollution control. In both cases, household consumption plays a minimal role in driving the demand for water.
Keywords: Q56; Q58; Q59; 330; mining; water use; water extraction; Philippines